ØÙƒÙ… ØªØ¹Ø²ÙŠØ± Ù…Ø§Ù†Ø¹ Ø§Ù„Ø²ÙƒØ§Ø© Ø¨Ø£Ø®Ø° Ø§Ù„Ù…Ø§Ù„ Ø¹Ù†Ø¯ Ø§Ù„Ù…Ø°Ø§Ù‡Ø¨ Ø§Ù„Ø£Ø±Ø¨Ø¹Ø© - Mukran H. Usman; Bukhari, Imran; Awal Rifai Wahab; Firdaus, Aris (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
Zakat obligation is matter in religion that are logically already known. Refusing to pay zakat due to ignorance and greed is one of the great sins in afterlife law, and is among the most heinous crimes in worldly law. This research discusses the law of takzir against people who are reluctant to pay zakat by taking their property according to the four schools. This research aims to find out the opinions of the four schools of jurisprudence about the law of takzir against people who are reluctant to pay zakat by taking their property (forcibly), and to know the understanding of disputes of opinion about the takzir against people who are reluctant to pay zakat by taking their property according to four schools. The research methods used in research are inductive-deductive and comparative methods. The results showed that the four schools of jurisprudence agreed to impose takzir on people who are reluctant to pay zakat by taking their property forcibly according to the obligatory zakat rate on it without additional. While some scholars consider that takzir for people who are reluctant to pay zakat is to take their property forcibly according to the obligatory zakat rate on it accompanied by additional punishment that takes half of its property. This is the opinion of the old Shafii (qaul qadÄ«m), one of the narration of Imam Ahmad, as well as the opinion of some scholars such as al-AuzÄÊ¿Ä«, Isá¸¥Äq bin RÄhÅ«yah, Ibn al-Ê¿Uá¹¡aimÄ«n, in addition to the opinion of the permanent of Fatwa Commission of the Kingdom of Saudi Arabia. As for the understanding of dissent in this matter is the knowledge that every school of jurisprudence has a proposition as a guideline to strengthen its opinion, so that the difference should not be the cause of division and hostility among the Muslims.